Positive selection and high sensitivity test for MYD88 mutations using locked nucleic acid. (21st January 2016) - Albitar, A.; Ma, W.; DeDios, I.; Estella, J.; Agersborg, S.; Albitar, M.
Summary: Introduction: Detection of mutations in the myeloid differentiation primary response gene 88 (MYD88) has clinical implications on diagnosis and therapy, especially in patients with Waldenström's macroglobulinemia (WM) and IgM monoclonal gammopathy of unknown significance (IgM‐MGUS). We describe a method that provides greatly increased sensitivity for detecting minority mutations in MYD88. Methods: We used a locked nucleic acid oligonucleotide to block amplification of wild‐type DNA during polymerase chain reaction (PCR). Sanger sequencing of amplified DNA was used for detecting mutations in MYD88 gene. This approach was used to test samples from patients with WM and IgM‐MGUS. Results: When compared to traditional PCR followed by Sanger sequencing, our methodology was significantly more sensitive (one mutant allele in a background of 200 wild‐type alleles). Using sequencing allowed us to visualize the PCR product, giving advantages over other methodologies such as allele‐specific PCR. Based on analyzing 36 randomly selected, MYD88 mutated, clinically tested samples, we demonstrate that traditional PCR failed to detect MYD88 mutations in 64% of the samples that were clearly positive by wild‐type blocking PCR. Conclusion: The new methodology is essential for attaining accurate results in clinical testing.